Biohumoral markers as predictor of right ventricular dysfunction in AL Amyloidosis. (June 2014) - Cappelli, Francesco; Baldasseroni, Samuele; Bergesio, Franco; Padeletti, Luigi; Attanà, Paola; Pignone, Alberto Moggi; Grifoni, Elisa; Ciuti, Gabriele; Fabbri, Alessia; Tarantini, Francesca; Marchionni, Niccolò; Gensini, Gian Franco; et al.
Abstract Aim: In AL amyloidosis, the importance of right ventricle (RV) involvement has recently been underlined and its role in predicting prognosis has been emphasized. Little is known about the relationship between RV involvement, N-terminal pro-brain natriuretic peptide (NT-proBNP) and troponin levels. Aim of our study was to clarify the relationship between NT-proBNP and troponin and RV involvement and analyze their independent value as predictors of RV dysfunction. Methods and Results: We examined 76 consecutive patients with biopsy-proven AL amyloidosis. Each patient received complete clinical evaluation, troponin I, NT-proBNP assay and comprehensive echocardiographic evaluation. Considering a tricuspidal annulus plane systolic excursion (TAPSE) value <16 mm, 23 patients (30%) presented RV systolic dysfunction, whereas 53 (70%) did not. Patient with reduced TAPSE had thicker left ventricle (LV) walls and RV free walls, reduced LV fractional shortening, impaired LV diastolic function and worse LV and RV myocardial performance index. For RV dysfunction the best predictive value for NT-proBNP was identified as 2977 ng/l with sensitivity and specificity of 87% and 84%, respectively; best cut-off for troponin I was identified as 0.085 ng/l, with sensitivity and specificity of 85% and 90% respectively. At multivariable logistic regression analysis, both NT-proBNP and troponin I emerged as independent predictors of RV dysfunction presence but troponin appears to have a higher predictive power. Conclusion: Our study demonstrated that cut-off values of 2977 ng/ml for NT-proBNP and 0.085 ng/l for troponin were able to identify a subgroup of AL patients with RV dysfunction. Troponin I is more accurate and seems to be the best biohumoral marker of RV dysfunction.